The effectiveness of the guided inquiry learning model assisted by picture card media in improving students' critical thinking skills in natural science subjects - Risma Risma; Andi Harpeni Dewantara (Institut Agama Islam Negeri (IAIN) Bone, 2022)
This study aims to describe students' critical thinking skills in natural science learning, the effectiveness of the guided inquiry learning model assisted by picture card media in improving students' critical thinking skills in natural science learning, and the difference between before and after using the media-assisted guided inquiry learning model. picture cards in improving students' critical thinking skills in learning natural sciences. This research is a quantitative pre-experimental design. The research design used is the One Group Pretest-Posttest Design pattern. This design has a pretest, before being given treatment. The data collection technique in this study used a multiple-choice test technique. The data in this study were analyzed using descriptive and inferential statistical analysis techniques. The results of this study indicate that students' critical thinking skills before being taught the guided inquiry learning model assisted by picture card media had an average of 37.31, a standard deviation of 19.299 and a percentage of completeness of 8% and after applying the guided inquiry learning model assisted by media picture students' critical thinking skills have an average of 73.46, a standard deviation of 9.356 and a completeness percentage of 81%; the guided inquiry learning model assisted by picture card media is effective in improving students' critical thinking skills in natural science learning (p-value 0.05); and there is a significant difference between before and after applying the guided inquiry learning model assisted by picture card media in improving students' critical thinking skills in learning natural sciences.